New Records of Flowering Plants for the Himalaya-I - Javeid, G. N. (Indian Forester, 1973)
Papaver macrostomum Boiss. and Huet (Papaveraceae), Rorippa sylvestris (L.) Besser, Cardamine flexuosa With. and Arabidiopsis pumila (Steph.) Busch. (Brassicaceae), and Torilis nodosa (L.) Gaetn. (Apiaceae) are described here as new records for the Himalaya. Calder et. al. (1926) published a list of species and genera of Indian phanerogames not included in Sir J.D. Hooker’s Flora British India (1872-1897). That list contained in all 1694 species from the then British India and Burma as additions to J.D. Hooker’s Flora and recorded upto 8924. A second list was published by Razi (1959) as a supplement to the Calder et. al. (1926) list. In this list 1595 species, recorded and described between 1924-1950 from India and Pakistan, were included. Recently Kitamura (1955) scanned the Eastern parts of the Himalayas and quite a number of new reports were made by him. During the course of the study of the flora of Srinagar and adjacent mountain ranges, the author came across several plants so far unknown from the Indian subcontinent. In the present series these species are described. The voucher specimens have been preserved in the Herbarium of the Botany Department, the University of Kashmir.